Essential Package of Palliative Care for Women With Cervical Cancer: Responding to the Suffering of a Highly Vulnerable Population. (2021) - Krakauer, Eric L.; Kane, Khadidjatou; Kwete, Xiaoxiao; Afshan, Gauhar; Bazzett-Matabele, Lisa; Ruthnie Bien-Aimé, Danta Dona; Borges, Lawrence F.; Byrne-Martelli, Sarah; Connor, Stephen; Correa, Raimundo; Devi, C. R. Beena; Diop, Mamadou; et al.
Abstract : Women with cervical cancer, especially those with advanced disease, appear to experience suffering that is more prevalent, complex, and severe than that caused by other cancers and serious illnesses, and approximately 85% live in low- and middle-income countries where palliative care is rarely accessible. To respond to the highly prevalent and extreme suffering in this vulnerable population, we convened a group of experienced experts in all aspects of care for women with cervical cancer, and from countries of all income levels, to create an essential package of palliative care for cervical cancer (EPPCCC). The EPPCCC consists of a set of interventions, medicines, simple equipment, social supports, and human resources, and is designed to be safe and effective for preventing and relieving all types of suffering associated with cervical cancer. It includes only inexpensive and readily available medicines and equipment, and its use requires only basic training. Thus, the EPPCCC can and should be made accessible everywhere, including for the rural poor. We provide guidance for integrating the EPPCCC into gynecologic and oncologic care at all levels of health care systems, and into primary care, in countries of all income levels.